Life experiences of patients before having hypertension: a qualitative study - Afzal Shamsi; Nahid Dehghan Nayeri; Maryam Esmaili (Electronic Physician, 2017)
Introduction: Identification of causes of hypertension on the basis of the perspectives and experiences of patients is the key to success in health plans of these patients. The aim of this study was to describe the experiences of life before becoming hypertensive patients. Methods: This qualitative study was conducted during August 2015 to April 2016. Twenty-seven hypertensive patients referred to hospitals affiliated to Tehran University of Medical Sciences were selected based on purposive sampling, and semi-structured in-depth interviews were conducted with them. The data were analyzed by the content analysis method and using qualitative data analysis software MAXqda 2011. Results: Three main categories were extracted from data analysis. Patients experienced factors such as negligence and neglect, life stress, lack of healthy lifestyles and abuse awareness, spirituality abandonee in the main category of “personal experience,” factors such as family conflicts, heredity, inappropriate nutritional and life style in the main category of “family life,” and also factors such as job stress, economic problems, urbanization, chemical agents during the war in the main category of “social life.” Conclusions: Based on the findings, patients before becoming hypertensive under the influence of their culture and beliefs had experienced many risk factors associated with hypertension. Comprehensive planning and appropriate to the cultural, social, and beliefs context about the prevention and correction of these factors is necessary.